2020
DOI: 10.3390/foods9101371
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Health-Promoting Bioactives in Broccoli and Methyl-Jasmonate Pre-Harvest Treatments to Enhance Their Contents

Abstract: Broccoli is a source of bioactive compounds that provide an important nutritional value. The content of these compounds can vary depending on agronomic and environmental conditions, as well as on elicitation. In this study, three crop trials were carried out to evaluate the effects of the cultivation season, the application of different dosages of methyl-jasmonate (MeJA) on the overall quality and on the total content of bioactive compounds of ‘Parthenon’ broccoli cultivated under the field conditions of south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
10
1
Order By: Relevance
“…Among them, broccoli ( Brassica oleracea var. italica ) has acquired considerable relevance in the last few years as a “therapeutic” food, since it contains pharmacologically active substances [ 16 , 17 ]. Many studies have been focused on broccoli florets, which represent only 15% of the total aerial biomass [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, broccoli ( Brassica oleracea var. italica ) has acquired considerable relevance in the last few years as a “therapeutic” food, since it contains pharmacologically active substances [ 16 , 17 ]. Many studies have been focused on broccoli florets, which represent only 15% of the total aerial biomass [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of research attention has been paid to sulforaphane, whose health properties are well established [14]. Available data have shown that the consumption of sprouts plays an important role in human health and reduces the risk of chronic diseases [10,11,13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Broccoli, which belongs to the group of important vegetable crops, is widely cultivated in the world and is rich in bioactive compounds and minerals [1][2][3]. Health benefits from broccoli are associated with high amounts of glucosinolates, isothiocyanates, phenolic compounds, ascorbic acid, tocopherols, carotenoids, and minerals including calcium, magnesium, sulphur, and selenium [4,5]. Phytochemicals occurring in vegetable crops mainly undergo genetic control and environmental conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Health benefits from broccoli are associated with high amounts of glucosinolates, isothiocyanates, phenolic compounds, ascorbic acid, tocopherols, carotenoids, and minerals including calcium, magnesium, sulphur, and selenium [4,5]. Phytochemicals occurring in vegetable crops mainly undergo genetic control and environmental conditions [5,6]. Apart from breeding strategies, agronomic methods to increase the content of bioactive components in broccoli are also being sought [1].…”
Section: Introductionmentioning
confidence: 99%